“It’s not what I saw, it’s not what I thought”: - Lindsey Dodd (Conserveries Mémorielles)
This article draws on the oral history narratives of three people who were children in France during the Second World War to demonstrate their dissatisfactions with dominant versions of this past put forward in authoritative public discourse. Rachel was a Jewish child, persecuted, abused, but saved; Anne-Marie was the daughter of a railway resistance fighter who was deported and killed; Grégoire was a child evacuee who survived a violent bombardment. At various moments of their adult lives, each experienced a disruptive form of dissociation with their (personal) history as lived and experienced in comparison with (national) History as researched and recounted. All three invested in healing this wound, in private and public ways. Norquay (1999) writes that forgetting is “an active process which can involve denial, refusal, discrediting, silencing, omitting”; this article shows the generative power of feeling forgotten, denied, refused, discredited, silenced or omitted, to inspire action which challenges hegemonic discourse. Central to its argument is a call to attend to what feelings do within societies. (AHMED, 2014) While much influential scholarship is dedicated to top-down analyses French post-war memorial culture (mémoire), less attention is given to personal souvenirs of “ordinary” or “unimportant” people, particularly those who were children; such voices and the claims they make have at times been characterised as competitive and damaging to the “coherence of the national narrative” (WIEVIORKA, 2012). Yet by failing to listen, dominant historical discourse may provoke damaging sentiments of resentment, exclusion and shame.